Intersectional vulnerabilities: Examining the impact of gender, age, and employment on gender-based violence during COVID-19 - Meli, Jacob Kipkoech (Research Journal in Advanced Social Sciences, 2024)
In the initial quarter of 2020, when the world entered a lockdown to curb the spread of Covid-19, cases of Gender-Based Violence (GBV) surged significantly. In Kenya, there was a documented increase of 36% in GBV incidents in 2020, highlighting a connection between the Covid-19 pandemic and the upswing in GBV occurrences (Ministry of Public Service and Gender, 2021). However, the notable rise in reported gender-based violence cases during the Covid-19 pandemic necessitates deeper exploration, particularly regarding how gender, age, and employment status combined to create vulnerabilities, leading to the occurrence or worsening of GBV. This study examined the impact of gender, age and employment status on Gender based violence during Covid-19 pandemic. The study was guided by intersectionality theory, which explains how gender, age and employment status. The study also adopted intersectionality theory, which explains the intersectionality of victim experiences and interventions. The study used a mixed-method research design, which gave it the advantage of using both quantitative and qualitative research to answer the research questions comprehensively. Kakamega Central Sub-County in Kakamega County served as the research site due to its diverse population and its high number of registered GBV cases during the pandemic. The sample size for this study was 270 GBV victims selected based on Taro Yamane's sample determination formula. The target sample size of key informants was 27. Quantitative data was analyzed using cross-tabulation and summary statistics, while qualitative data was analyzed thematically using content analysis. Intersectionality was evident in the experience of GBV among victims based on gender (indicated by 93.70% of GBV victims), age (75.70%), and employment status (74.40%). As a result, the study recommendations emphasize the importance of: Enhancing resilience among vulnerable groups; Allocating additional resources to GBV response teams; Adopting an intersectionality lens to address diverse victim experiences; and, developing tailored intervention measures responsive to individual needs. The study's conclusions will inform policy evaluation and address the knowledge gap identified so as to refocus efforts to address the intersectionality factors that contribute to GBV in pandemics like Covid-19.